Synthesis of Nickel In Situ Modified SAPO-11 Molecular Sieves and Hydroisomerization Performance of Their NiWS Supported Catalysts - Dai, Xiaojun; Cheng, Yan; Si, Meng; Wei, Qiang; Zhao, Luyuan; Wang, Xiaohan; Huang, Wenbin; Liu, Haoran; Zhou, Yasong (Frontiers in Chemistry, 2021)
SAPO-11 molecular sieves were modified with different Ni content by the in-situ modification method. The Ni modified SAPO-11 molecular sieves were used as the supports to prepare the corresponding NiW supported catalysts for the hydroisomerization of n-hexadecane. The Ni modified SAPO-11 and the corresponding NiW supported catalysts were characterized by XRD, SEM, N2 adsorption-desorption, NH3-TPD, Py-IR, HRTEM and XPS. The results showed that Ni in-situ modification preserve the crystal structure of SAPO-11, increased the BET specific surface area, mesopore volume and medium and strong Brønsted acid amount of SAPO-11, and increased the stacking number of active phase of the catalysts. 3Ni-SAPO-11 possessed the largest the BET specific surface area, mesopore volume and medium and strong Brønsted acid amount. NiW/3Ni-SAPO-11 possessed the highest dispersion of active phase and the highest sulfidation degree of the active metals. The results of the hydroisomerization of n-hexadecane showed that Ni in-situ modification improved the catalytic activity and selectivity of the catalysts for the hydroisomerization of n-hexadecane to varying degrees. Especially, NiW/3Ni-SAPO-11 had the highest catalytic activity and isomer selectivity, and the maximum yield of isomeric hexadecane could reach 71.18%.